MEANING COST CEREMONY MOME’ATI (BEAT) IN PUBLIC GORONTALO - Mariyana Ilaponu; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (International Journal of Innovations in Engineering Research and Technology, 2023)
Study This aim For know the meaning of fee in the Mome’ati (beating) Ceremony on public Gorontalo use approach Phenomenology. custom mom’ati is Wrong One custom Which held when a Woman Already get hindrance (period). Research methods This use method study qualitative with with approach Phenomenology. Methods of data collection carried out with method interview, observation, and documentation .From the results of these studies indicate that There is four meaning cost Which contained in ceremony Mom’ati (beating) public Gorontalo namely: Gratitude, Blessing, Friendship Event, And sincerity .